How does nutrition education contribute to the consumers' use and attitudes towards food labels? - Ayaz, Aylin; Dedebayraktar, Damla; Inan-Eroglu, Elif; Besler, Halit Tanju; Buyuktuncer, Zehra (Emerald Group Publishing Ltd, 2021)
Purpose This study aims to determine the effects of nutrition knowledge on the use of nutrition facts labels in emerging adults by defining the nutrition education status. Design/methodology/approach For this cross-sectional study, 919 young adults, aged 18-24 years, were recruited. Participants trained by dietetic professional at least 2 h per week during the period of at least one education period were considered as having nutrition education. Food label use, specific circumstances and different food products were recorded. The participants were also asked about their attitudes regarding food label use with a questionnaire including 15 products. Findings Nutrition facts label is mainly used when buying a product for the first time, a product of an unknown brand or comparing different companies' similar products, regardless of nutrition education status. Participants with nutrition education had a higher nutrition facts label use and they use the score for specific food products including breakfast cereal (p= 0.003), snacks (p< 0.001), beverages (p= 0.004), ready to eat soups (p= 0.004) and diet products for special occasions (p< 0.001). Mean total score of attitudes regarding food label use for participants who had nutrition education was found as 58.9 +/- 6.1 and who did not have nutrition education was found as 51.7 +/- 9.2 (p< 0.01). Originality/value Nutrition education, which is related to the nutrition facts label use, would be especially useful in helping people for the selection of healthier foods. As habits acquired from childhood will last for a lifetime, more effective nutrition education programs and nutrition label reading education programs should be designed. The findings need to be considered for promoting nutrition facts label use by developing nutrition education.
Keywords: Education; Nutrition; Young adults; Food label